An Unusual Granular Cell Tumour of the Buttock and a Review of Granular Cell Tumours - Sharad P. Paul; Vladimir Osipov (Case Reports in Dermatological Medicine)
Granular cell tumours, first described by Abrikossoff in 1926, are known to occur in skin, connective tissue, breast, gastrointestinal and genital tracts. While they are rare, they are more common in people of African descent and show a slight female preponderance, usually presenting as solitary and painless masses. Less than 10% of occurrences are multiple, and fewer than 3% of tumours behave in a malignant fashion. The mean age, at presentation, is 40–60 years. We report a case of granular cell tumour in a young white male presenting with a painful soft tissue tumour in his buttock. The presentation is unusual because of the age, patient demographic, body site, and clinical presentation. The clinical and histological aspects are reviewed in the context of this clinical case and the associated literature.